A critical step for postsynaptic F-actin organization: Regulation of Baz/Par-3 localization by aPKC and PTEN - Ramachandran, Preethi (2009)
Actin remodeling has emerged as a critical process during synapse development and plasticity. Thus, understanding the regulatory mechanisms controlling actin organization at synapses is exceedingly important. Here we used the highly plastic Drosophila neuromuscular junction (NMJ) to understand mechanisms of actin remodeling at postsynaptic sites. Previous studies have suggested that the actiinding proteins Spectrin and Coracle play a critical role in NMJ development and the anchoring of glutamate receptors most likely through actin regulation. Here we show that an additional determinant of actin organization at the postsynaptic region is the PDZ protein Baz/Par-3. Decreasing Baz levels in postsynaptic muscles has dramatic consequences for the size of F-actin and spectrin domains at the postsynaptic region. In turn, proper localization of Baz at this site depends on both phosphorylation and dephosphorylation events. Baz phosphorylation by its binding partner, atypical Protein Kinase C (aPKC), is required for normal Baz targeting to the postsynaptic region. However, the retention of Baz at this site depends on its dephosphorylation mediated by the lipid and protein phosphatase PTEN. Misregulation of the phosphorylation state of Baz by genetic alterations in PTEN or aPKC activity has detrimental consequences for postsynaptic F-actin and spectrin localization, synaptic growth, and receptor localization. Our results provide a novel mechanism of postsynaptic actin regulation through Baz, governed by the antagonistic actions of aPKC and PTEN. Given the conservation of these proteins from worms to mammals, these results are likely to provide new insight into actin organization pathways.